Groundwater Quality Assessment of Ambuliyar Watershed using GIS - Devi R, Keerthana; D, Balaji; H, Natarajan; N, Nasir; R, Selvakumar (International Journal of Engineering and Technology, 2018)
Groundwater is significant in satisfying domestic and agricultural needs.Besides scarcity, the groundwater resource is degrading drastically around the world. The Ambuliyar watershed falling in parts of Tamil Nadu also faces similar problems. To decipher the quality degradation, pre-monsoon and post-monsoon data on various physical and chemical parameters was collected for 29 wells for the year 2014 from Public Works Department. Spatial maps were generated on the above geochemical parameters and categorized into five classes using GIS software. Weights were assigned for each parameter based on their relative importance in with each other parameters. Finally, quality index map was generated by integrating them, and subsequently their aerial extent in monsoons was worked out. During the post-monsoon period, 18% of the study area represents â€œexcellentâ€, 46% â€œgoodâ€, 25% shows â€œmoderateâ€ and 11% shows â€œpoorâ€ quality. While during pre-monsoon period, 34% of the area exhibits â€œexcellentâ€, 43% â€œ moderateâ€, and the remaining 23% of â€œpoorâ€.Â Â Â Â